(untitled) (Lapai Journal of Economics, 2020)
The study investigated exchange rate and its impact on export performance in Nigeria. Using secondary data spanning from 1986 – 2018, the study adopted the Error Correction Mechanism (ECM) and employed export as the dependent variable while foreign exchange rate, inflation rate, interest rate, gross capital formation as independent variables. The unit root test to ascertain the stationarity level of variables and the Johansen Cointegration test to check for long run relationship between variables were employed. Findings from the result showed that exchange rate had a significant and negative relationship with export performance in Nigeria both in the short and long run. The study therefore, recommends that exchange rate should be closely monitor and managed given the implications of its movements on exports. Also, government should propose and implement policies that will stabilise the exchange rate as this will help in the reduction of undesirable impact of exchange rate fluctuations on export performance.